Human in vitro eugenics: close, yet far away - da Fonseca, Flávio Guimarães; Ribeiro, Daniel Mendes; Carvalho, Nara Pereira; Stancioli, Brunello (Journal of medical ethics, 2014)
In meiosis, heterozygous genes segregate differently to form different gametes. [...]numerous other processes become activated during meiosis in order to provide the individual with the largest possible array of genetically diverse gametes. All this complex net of tissue-to-tissue cross-talking will simply not happen if generations are shortened down to the embryogenic level before the next generation starts from cells of the previous one. [...]after something like 20 in vitro generations, will a disease manifest in the 21st subject as it would after 20 real generations?